In Vitro Investigation of Statin Effects on Genes Associated with Severe COVID-19 in Cancerous and Non-Cancerous Cells - Kapustová, Adriana; Macášek, Patrik; Baďurová, Bibiána; Melegová, Jana; Rimpelová, Silvie; Kubovčiak, Jan; Šáchová, Jana; Hradilová, Miluše; Kolář, Michal; Vítek, Libor; Ruml, Tomáš; Gbelcová, Helena (Biomedicines, 2025)
Background: The progressive course of coronavirus disease 2019 (COVID-19) is more frequently observed in individuals with obesity, diabetes, pulmonary and cardiovascular disease, or arterial hypertension. Many patients with these conditions are prescribed statins to treat hypercholesterolaemia. However, statins exhibit additional pleiotropic effects. The present study aims to investigate the effects of all eight currently existing statins on the expression of genes whose products have been reported to be directly associated with complicated COVID-19 disease. Methods: We extended the interpretation of the whole-genome DNA microarray analyses of pancreatic cancer cells MiaPaCa-2 and whole-transcriptome analyses of adipose tissue-derived mesenchymal stem cells AD-MSC that we had performed in the past. From the number of genes with altered expression induced by statins, we focused on those reported to be involved in a complicated course of COVID-19, including APOE and ACE2, genes encoding proteins involved in innate antiviral immunity and respiratory failure genes. Results: Although we did not observe statin-induced changes in the expression of APOE, ACE2 and any of the six genes clustered in the locus associated with respiratory failure in patients with COVID-19, some statins induced changes in the expression of genes encoding their interaction partners. Among genes associated with the immune system, all statins, which are effective in vitro affected the expression of genes encoding IL-6 and IL-8 and interaction partners of NF-kB, which may influence the duration of viral persistence. Conclusions: Statins act on multiple pathways simultaneously, some of which support COVID-19 development, while others suppress it.
Keywords: APOE; COVID-19; statins; ACE2; microarray analyses; gene expression